The Emerging Role of Epigenetic Methylation in Kidney Disease - Wen, Li; Yang, Hong-liu; Lin, Lin; Ma, Liang; Fu, Ping (Current Medicinal Chemistry, 2022)
Kidney disease has complex and multifactorial pathophysiology and pathogenesis. Recent studies have revealed that epigenetic methylation changes, namely DNA methylation, histone methylation and non-histone methylation, are strongly implicated in various forms of kidney diseases. This review provides a perspective on the emerging role of epigenetic methylation in kidney disease, including the effects of DNA methylation in diverse promoter regions, regulation and implication of histone methylation, and recent advances and potential directions related to non-histone methylation. Monitoring or targeting epigenetic methylation has the potential to contribute to development of therapeutic approaches for multiple kidney diseases.
Keywords: kidney diseases